Prediction of Life Expectancy in Aceh Province by District City Using the Cyclical Order Algorithm - Teuku Afriliansyah; Z Zulfahmi (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
Indicators to evaluate the role of the local and central government in the welfare of its population, especially in the health sector, can be seen from the life expectancy of the community. Therefore the aim of this study is to predict the life expectancy of the Acehnese using the Cyclical Order Weight / Bias Algorithm. This study uses life expectancy data for the population of Aceh in 2010-2019 based on city districts consisting of 23 regions, which were obtained from the Aceh Central Statistics Agency. This study uses 6 architectural models, including: 8-5-1, 8-6-1, 8-7-1, 8-8-1, 8-9-1 and 8-10-1. After analyzing and calculating the 6 architectural models, the 8-9-1 model was chosen as the best with an accuracy rate of 91% and MSE testing 0.0010800577. The results of this study are in the form of the best architectural model that can be used to predict the life expectancy of the Acehnese people.